Drosophila melanogaster chemical ecology revisited: 2-D distribution maps of sex pheromones on whole virgin and mated flies by mass spectrometry imaging - Filip Kaftan; Purva Kulkarni; Markus Knaden; Sebastian Böcker; Bill S. Hansson; Aleš Svatoš (BMC Zoology, 2020)
Abstract Background Sexual behavior in Drosophila melanogaster flies is greatly influenced by chemical cues. In this study, a spatial distribution of female and male sex pheromones was investigated on the surface of virgin and mated six-day-old fruit flies. Surface analysis was performed using the technique of mass spectrometry imaging (MSI) matrix-assisted laser desorption/ionization – time of flight (MALDI-TOF) and confirmed by gas chromatography – mass spectrometry (GC-MS) analysis of hexane extracts prepared from dissected flies. Results MALDI-TOF MSI experiments focused on female pheromones (7Z,11Z)-heptacosa-7,11-diene (7,11-HD) and (7Z,11Z)-nonacosa-7,11-diene (7,11-ND) were enhanced by using lithium 2,5-dihydroxybenzoate (LiDHB) matrix to improve the ionization and quality of MS spectra. Oxygenated compounds represented by male anti-attractants 11-cis-vaccenyl acetate (cVA) and 3-O-acetyl-1,3-dihydroxy-octacosa-11,19-diene (CH503) were successfully ionized without MALDI matrix in the form of potassium adducts in laser desorption ionization (LDI-TOF MSI) mode. A similar pattern of distribution for 7,11-HD and 7,11-ND was observed on the surface of both the left and the right female wing, with the strongest signals at the base of the wing. 7,11-HD and 7,11-ND were additionally detected on female legs but not on the body. The distribution of both male pheromones, cVA and CH503, was localized in virgin male flies solely on the abdominal tip and anogenital region. In addition, results from MSI experiments with mated flies showed the distribution of cVA and CH503 also on the female abdomen and thorax, demonstrating that anti-attractants were transferred from males to females during copulation. Results from LDI/MALDI-TOF MSI were supported by GC-MS analysis of hexane extracts prepared from different parts of virgin male or female Drosophila flies. Similar amounts of 7,11-HD and 7,11-ND were present on the legs, body and wings (127 ± 5 ng and 170 ± 8 ng, respectively). cVA was detected only on the male body. All acquired MSI datasets were affected by mass shift (predominantly between ±0.2 Da to ±0.4 Da), which was reduced using a mass recalibration approach. Conclusions The LDI/MALDI-TOF MSI technique makes it possible to study the distribution of female and male sexual pheromones on D. melanogaster flies. Moreover, the technique enables the transfer of male sex pheromones to females during copulation to be visualized. However, imaging experiments of 3-D biological samples performed on a single TOF-MS instrument equipped with a MALDI ion source and UV nitrogen laser evinced a photo-electric charging/discharging, a phenomenon that often leads to unpredictable mass shifts and poor mass accuracy.